PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP KINERJA KEUANGAN (ROE) DENGAN MANAJEMEN LABA DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Untuk Periode 2011-20 - Rully Aprianto; Desmiyawati '; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This research is to investigate the influence of Corporate Social Responsibility (CSR) to corporate financial performance with earning management and size company as moderating variable. CSR disclosure by GRI G3 is used as the proxy of CSR activity, ROE is used as the proxy of financial performance and discretionary accruals by The Modified Jones model is used as the proxy of earning management practices. The results of this research show that CSR has significant influence on corporate financial performance. The analysis with the moderating variable Absolute Residual Method shows that earning management moderate in relation between CSR and corporate financial performance and it shows negative significant influence. And The analysis with the moderating variable Absolute Residual Method shows that size company moderate in relation between CSR and corporate financial performance and it shows positive significant influence.Keywords: Corporate Social Responsibility, earnings management, size company, and corporate financial performance